'I could have made those changes years earlier': experiences and characteristics associated with receiving a prediabetes diagnosis among individuals recently diagnosed with type 2 diabetes. (27th November 2019) - Somerville, Mari; Burch, Emily; Ball, Lauren; Williams, Lauren T
Abstract: Background: Prediabetes increases the risk of developing type 2 diabetes (T2D). Improving diet quality is key in preventing this progression, yet little is known about the characteristics of individuals with prediabetes or the nutrition care they receive. Objectives: This study aims to identify characteristics and experiences associated with receiving a prediabetes diagnosis prior to developing T2D. Methods: A mixed methods study encompassed a quantitative subanalysis of participants with newly diagnosed T2D from The 3D Study, and semi-structured telephone interviews with a subsample of participants who were previously diagnosed with prediabetes. Interviews were thematically analysed and survey data synthesized using SPSS statistical software. Results: Of the 225 study participants, 100 individuals were previously diagnosed with prediabetes and 120 participants were not. Those with prediabetes were less likely to be smokers ( P = 0.022) and more likely to be satisfied with seeing a dietitian ( P = 0.031) than those without a previous prediabetes diagnosis. A total of 20 participants completed semi-structured interviews. Thematic analysis revealed three themes: (i) experiencing a prediabetes diagnosis; (ii) receiving nutrition care during prediabetes and (iii) reflecting on the experience of receiving care for prediabetes versus T2D. Conclusions: There are gaps in the current management of prediabetes in Australia. Low rates of prediabetes diagnosis and an ambiguous experience of receiving this diagnosis suggest an area of health service improvement. With no difference in diet quality between individuals with and without a previous prediabetes diagnosis, the nutrition care during prediabetes may be more important than the diagnosis itself in delaying the onset of T2D.